Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/aej.12115
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic fatigue analysis of Reciproc R25® instruments with different kinematics

Abstract: This study aimed to compare the cyclic fatigue resistance of Reciproc® instruments when used with different kinematics (150° counterclockwise (CCW)-30° clockwise (CW), 270° CCW-30° CW, 360° CCW-30° CW and continuous rotation). Various kinematics were tested in steel canals with a 3 mm radius and a 60° angle of curvature as follows (n = 20): 150° CCW-30° CW, 270° CCW-30° CW, 360° CCW-30° CW and 360° CCW (rotary motion). Reciproc R25® instruments were used until fracture occurred. The time to fracture was record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The results showed that WO instrument used in reciprocating motion had a greater resistance to cyclic fatigue. Arslan et al (2015) investigated the cyclic fatigue resistance of Reciproc â instruments used with different kinematics whether in reciprocating motion (150°c ounterclockwise (CCW)-30°clockwise (CW), 270°C CW-30°CW, 360°CCW-30°CW) or in continuous rotation using a static testing set-up. All reciprocating motions resulted in a longer mean duration to failure compared to continuous rotation.…”
Section: Search Basismentioning
confidence: 99%
“…The results showed that WO instrument used in reciprocating motion had a greater resistance to cyclic fatigue. Arslan et al (2015) investigated the cyclic fatigue resistance of Reciproc â instruments used with different kinematics whether in reciprocating motion (150°c ounterclockwise (CCW)-30°clockwise (CW), 270°C CW-30°CW, 360°CCW-30°CW) or in continuous rotation using a static testing set-up. All reciprocating motions resulted in a longer mean duration to failure compared to continuous rotation.…”
Section: Search Basismentioning
confidence: 99%
“…The NCF is useful for comparing different rotary instruments; however, it is not suitable for comparing the performance of different motions (11). Accordingly, previous studies have shown that changing the kinematics of the reciprocating motion can significantly affect the fracture resistance of NiTi instruments (7,(24)(25)(26)(27)(28)(29)(30). Thus, in the present study, the results were expressed as the time to fracture.…”
Section: Discussionmentioning
confidence: 94%
“…Differing outcomes in the fatigue resistance of instruments have also been described between similar RR motions, that is, when comparing Reciproc versus Waveone (24,25), and between single motions, for example, AR versus CR and RR versus CR (11,(26)(27)(28). Differing outcomes in the fatigue resistance of instruments have also been described between similar RR motions, that is, when comparing Reciproc versus Waveone (24,25), and between single motions, for example, AR versus CR and RR versus CR (11,(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fracture of the motor-driven rotary instrument is produced in two ways: cyclic fatigue, and torsional fatigue. Cyclic-fatigue fracture occurs when the instruments rotate freely in a curvature, generating tension/compression cycles in the region of maximal flexure until fracture (7,8). The incidence of fracture by cyclic fatigue in handheld instruments is 1-6% as compared with that of rotary instruments, which is 0.4-5% (9-11).…”
Section: Duringmentioning
confidence: 99%